SARS-CoV-2 Antibody Avidity Responses in COVID-19 Patients and Convalescent Plasma Donors. (10th September 2020) - Benner, Sarah E; Patel, Eshan U; Laeyendecker, Oliver; Pekosz, Andrew; Littlefield, Kirsten; Eby, Yolanda; Fernandez, Reinaldo E; Miller, Jernelle; Kirby, Charles S; Keruly, Morgan; Klock, Ethan; Baker, Owen R; et al.
Abstract: Background: Convalescent plasma therapy is a leading treatment for conferring temporary immunity to COVID-19–susceptible individuals or for use as post-exposure prophylaxis. However, not all recovered patients develop adequate antibody titers for donation and the relationship between avidity and neutralizing titers is currently not well understood. Methods: SARS-CoV-2 anti-spike and anti-nucleocapsid IgG titers and avidity were measured in a longitudinal cohort of COVID-19 hospitalized patients (n = 16 individuals) and a cross-sectional sample of convalescent plasma donors (n = 130). Epidemiologic correlates of avidity were examined in donors by linear regression. The association of avidity and a high neutralizing titer (NT) were also assessed in donors using modified Poisson regression. Results: Antibody avidity increased over duration of infection and remained elevated. In convalescent plasma donors, higher levels of anti-spike avidity were associated with older age, male sex, and hospitalization. Higher NTs had a stronger positive correlation with anti-spike IgG avidity (Spearman ρ = 0.386; P  < .001) than with anti-nucleocapsid IgG avidity (Spearman ρ = 0.211; P  = .026). Increasing levels of anti-spike IgG avidity were associated with high NT (≥160) (adjusted prevalence ratio = 1.58 [95% confidence interval = 1.19–2.12]), independent of age, sex, and hospitalization. Conclusions: SARS-CoV-2 antibody avidity correlated with duration of infection and higher neutralizing titers, suggesting a potential alternative screening parameter for identifying optimal convalescent plasma donors. Abstract : Evaluation of antibody avidity from potential convalescent plasma donors and hospitalized COVID-19 patients suggests increased SARS-CoV-2 IgG avidity is associated with being older, male, and hospitalized. Avidity is correlated with neutralizing titers offering a potential screening parameter for convalescent donors.